2023
DOI: 10.3390/app131810208
|View full text |Cite
|
Sign up to set email alerts
|

Remediation Opportunities for Arsenic-Contaminated Gold Mine Waste

Julie A. Besedin,
Leadin S. Khudur,
Pacian Netherway
et al.

Abstract: Arsenic (As)-contaminated gold mine waste is a global problem and poses a significant risk to the ecosystem and community (e.g., carcinogenic, toxicity). Arsenic concentrations of 77,000 mg/kg and 22,000 mg/kg in mine waste have been reported for Canada and Australia, respectively. Research is investigating environmentally sustainable techniques to remediate As-rich mine waste. Biological techniques involving plants (phytoremediation) and soil amendments have been studied to bioaccumulate As from soil (phytoex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 143 publications
0
1
0
Order By: Relevance
“…Mining activities-for example, gold mining-represent one of the main anthropogenic sources of As. Gold (Au) extraction methods, such as refractory ores and free-milling ores, produce As wastes in the form of gas, leachate, and calcinated soil, which pose significant environmental risks [3,4]. It has been reported that, globally, the cumulative As production as a result of mining activities increased from 0.06 to 3.29 million tonnes between 1900 and 2000 [5]; numerous studies indicate increasing As pollution as a result of mining in many countries [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Mining activities-for example, gold mining-represent one of the main anthropogenic sources of As. Gold (Au) extraction methods, such as refractory ores and free-milling ores, produce As wastes in the form of gas, leachate, and calcinated soil, which pose significant environmental risks [3,4]. It has been reported that, globally, the cumulative As production as a result of mining activities increased from 0.06 to 3.29 million tonnes between 1900 and 2000 [5]; numerous studies indicate increasing As pollution as a result of mining in many countries [6,7].…”
Section: Introductionmentioning
confidence: 99%